Male involvement interventions influencing maternal reproductive health outcomes: a narrative synthesis using RE-AIM with implications for maternal mortality in Africa - Anikamadu, Onyekachukwu; Nwaozuru, Ucheoma; Obodoechina, Nkiruka; Olusanya, Olufunto; Ojo, Temitope; Iwelunmor, Juliet (Frontiers in Health Services, 2025)
IntroductionMale involvement is crucial in optimizing maternal reproductive health outcomes, offering the potential to bolster reproductive health outcomes for mothers. The Reach, Effectiveness, Adoption, Implementation, and Maintenance (RE-AIM) framework can describe the implementation of interventions focused on promoting male involvement in maternal reproductive health. This study aims to (1) examine the implementation of male involvement interventions that influence maternal reproductive health outcomes and (2) report the implementation outcomes as conceptualized in the RE-AIM framework.MethodsThis protocol followed the preferred reporting items for systematic review and meta-analysis. We searched PubMed, CINAHL, PsycINFO, and Web of Science utilizing a systematic review with narrative synthesis methodology to identify studies describing interventions that promote male involvement in maternal reproductive health outcomes in Africa from 2000 to 2024 Furthermore, we evaluated the public health impact of male involvement interventions from selected studies using the RE-AIM framework. Two reviewers independently screened articles, selected eligible studies, and extracted data. The quality of included studies was assessed using the NIH Assessment Tool for Observational Cohort and Cross-Sectional Studies.ResultsThis review included six studies that met the inclusion criteria. Overall, the studies reported increased maternal reproductive health indicators (e.g., antenatal care uptake, antiretroviral medication adherence, and postnatal care uptake) after implementing the male involvement-focused interventions. The most commonly reported RE-AIM dimensions were Reach (83.4%) and Efficacy/Effectiveness (70%). Adoption (40.5%), Implementation (38.9%), and Maintenance (13.3%) were less often reported. All studies reported on measures of primary outcomes, intervention duration and frequency, sample size, and participants’ characteristics. However, few reported on implementation fidelity, quality of life, methods used to identify staff, staff inclusion/exclusion criteria, implementation cost, and maintenance indicators.ConclusionsThe review underscores the potential of male-involvement interventions in advancing maternal reproductive health outcomes. However, the limited reporting of external validity indicators such as intervention fidelity, intervention cost, and maintenance indicators limits such interventions’ scalability and long-term sustainability. This calls for more focus on reporting external validity indicators to inform the scalability and transferability of such interventions in real-world settings.Systematic Review Registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD420251031192, PROSPERO CRD420251031192.